Effects of Blast Overpressure on Neurons and Glial Cells in Rat Organotypic Hippocampal Slice Cultures - Miller, Anna P.; Shah, Alok S.; Aperi, Brandy V.; Budde, Matthew D.; Pintar, Frank A.; Tarima, Sergey; Kurpad, Shekar N.; Stemper, Brian D.; Glavaski-Joksimovic, Aleksandra (Frontiers in Neurology, 2015)
Due to recent involvement in military conflicts, and an increase in the use of explosives, there has been an escalation in the incidence of blast-induced traumatic brain injury (bTBI) among US military personnel. Having a better understanding of the cellular and molecular cascade of events in bTBI is prerequisite for the development of an effective therapy that currently is unavailable. The present study utilized organotypic hippocampal slice cultures (OHCs) exposed to blast overpressures of 150 kPa (low) and 280 kPa (high) as an in vitro bTBI model. Using this model we further characterized the cellular effects of the blast injury. Blast-evoked cell death was visualized by a propidium iodide (PI) uptake assay as early as 2 h post-injury. Quantification of PI staining in the cornu Ammonis 1 and 3 (CA1 and CA3) and the dentate gyrus (DG) regions of the hippocampus at 2, 24, 48, and 72 h following blast exposure revealed significant time dependent effects. OHCs exposed to 150 kPa demonstrated a slow increase in cell death plateauing between 24 and 48 h, while OHCs from the high blast group exhibited a rapid increase in cell death already at 2 h, peaking at approximately 24 h post-injury. Measurements of lactate dehydrogenase (LDH) release into the culture medium also revealed a significant increase in cell lysis in both low and high blast groups compared to sham controls. OHCs were fixed at 72 h post-injury and immunostained for markers against neurons, astrocytes, and microglia. Labeling OHCs with PI, neuronal, and glial markers revealed that the blast evoked extensive neuronal death and to a lesser extent loss of glial cells. Furthermore, our data demonstrated activation of astrocytes and microglia cells in low and high blasted OHCs, which reached a statistically significant difference in the high blast group. These data confirmed that our in vitro bTBI model is a useful tool for studying cellular and molecular changes after blast exposure.